Bibliometric Analysis of Inclusive Education Implementation Using Qualitative Descriptive Methods - Elyakim Nova Supriyedi Patty; Yorman Yorman; Sri Astuti Iriyani; Deshinta Arrova Dewi (Jurnal Pemberdayaan Masyarakat, 2025)
Inclusive education is a key component in achieving equitable and quality learning for all, yet its implementation in Indonesia still faces significant challenges. This study aims to analyze the dynamics, challenges, and opportunities of inclusive education in Indonesia while identifying gaps between existing policies and actual practices. Using a qualitative descriptive approach combined with bibliometric analysis, this research examines 100 articles indexed by Google Scholar from 2021 to 2025. Data were collected using the Publish or Perish application and analyzed using VOSviewer to map publication trends, co-authorship networks, and the most cited articles. Results indicate that while inclusive education policies exist, their implementation is hindered by inadequate infrastructure, limited teacher competencies, and insufficient curriculum flexibility. A significant decrease in research output after 2022 suggests a need for renewed academic interest and policy support. The study concludes that more targeted teacher training and adaptive curriculum design are essential for advancing inclusive practices. This research contributes to the scientific literature by offering a novel bibliometric overview and proposing actionable strategies to bridge the gap between policy and practice in inclusive education.